Efficacy of functional electrical stimulation alone and as an adjunct to exercise for improving respiratory function and aerobic capacity in spinal cord injury: a systematic review and meta-analysis - Xiangli, Jiahao; Ma, Binquan; Liang, Yu; Haijiangshi, Shi; Liu, Xifang (Frontiers in Rehabilitation Sciences, 2025)
ObjectiveTo systematically evaluate the efficacy of functional electrical stimulation (FES), used either alone or as an adjunct to exercise (rowing/cycling), for improving respiratory function and aerobic capacity in patients with spinal cord injury (SCI).MethodsWe conducted a PRISMA-compliant meta-analysis, searching PubMed, Embase, Cochrane Library, and Web of Science through January 2025. We included 23 randomized controlled trials and self-controlled studies (N = 314) that assessed outcomes such as forced vital capacity (FVC), peak expiratory flow (PEF), maximal expiratory/inspiratory pressure (MEP/MIP), and peak oxygen uptake (VO₂peak).ResultsWhen used as a standalone intervention, FES significantly improved expiratory function, with notable increases in PEF (SMD = 0.42, p = 0.007), MEP (SMD=0.93, p = 0.008), and FVC (SMD = 0.37, p = 0.03). However, no significant improvement was found for MIP (p = 0.38). When FES was combined with exercise, it significantly enhanced aerobic capacity. This was demonstrated by improvements in VO₂peak for both FES-assisted rowing (SMD = 0.35, p = 0.03) and FES-assisted cycling (SMD = 0.24, p = 0.0003) compared to exercise alone. No significant effects on peak ventilation were observed.ConclusionFES moderately improves key expiratory functions in individuals with SCI and acts synergistically with exercise to augment aerobic capacity. These findings support the clinical use of FES in this population. However, the interpretation of these results should consider the methodological heterogeneity across studies and the limited sample size for some outcomes.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/myprospero, identifier CRD420251030235.